Online counseling and its feasibility for couples and family (Actual Problems of Psychology in Educational Institutions, 2021)
The article clarifies the terminology, related to onlinecounseling, analyzes the opportunities of the counseling and onlinepsychotherapy, particularly in working with a couple and family,257Actual Problems of Psychology in Educational Institutions. 2021. Issue 11considers their advantages, including anonymity, confidentiality, security;accessibility, mobility, expanding the vision of the therapeutic context; anopportunity of using the most methods, the same as in offline counseling.The article clarifies researches, which proves the effectiveness of consultingonline, defines the main problems, which clients discuss during onlinecounseling, provides practical recommendations regarding the organizationof the online counseling process and the consideration of the limitations.of working in this way, defines the strategies of the behavior in case oftechnical problems during providing psychological assistance
Keywords: online-counseling, counseling for couples and families, internet-counseling, teletherapy, remote-counseling, e-psychotherapy; online-counseling